Analysis of the Stresses in Corrugated Sheets under Bending - Molina, Julio Cesar [UNESP]; Fiorelli, Juliano; Savastano, Holmer (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
This paper presents three different numerical models for the evaluation of the stresses in corrugated sheets under bending. Regarding the numerical simulations different approaches can be considered, i.e., a elastic linear analysis or a physical nonlinear analysis, that considers criteria to fail for the sheet material. Moreover, the construction of the finite element mesh can be used shell elements or solid elements. The choice of each finite element must be made from the consideration of their representativity before behavior to be simulated. Thus, the numerical modelling in this manuscript was performed from the three-dimensional models using the SAP2000Nonlinear software, version 7.42, which has as base the finite elements method (FEM). It was considered shell elements in the build the mesh of finite elements and an analysis of type elastic linear in this case. Five mm thick sheets were evaluated considering three different longitudinal dimensions (spans), i.e., 1100 mm, 1530 mm and 1830 mm. The applied load to the models was 2500 N/m and it was verified that the spans of support of sheets have a significant influence on the results of stresses. The sheets with larger spans present larger stresses for the same applied load. The most intense values of tension occur in the troughs (low waves) of the sheets, on the lower surface, while the most intense values of compression occur in the crests (high waves), on the upper surface of the sheet. The flanks, which are the parts among the troughs and crests of the sheets, are submitted to low levels of stresses. The numeric results of the stresses showed a good agreement with the results obtained from other researchers(3) and these results can be used to predict the behavior of corrugated sheets under bending.
Keywords: corrugated sheet; numerical modelling; stress analysis